Erdély felekezeti helyzete egy utazó jezsuita szemével a 16. század végén. Antonio Possevino Commentario di Transilvania című művének értelmezése - LUKÁCS, Olga (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
The Confessional Landscape of Transylvania through the Eyes of a Travelling Jesuit at the End of the Sixteenth Century. An Interpretation of Antonio Possevino’s Commentario di Transilvania. This article offers a source-critical reading of Antonio Possevino’s Commentario di Transilvania, arguing that the text should be approached primarily as a strategically crafted report addressed to the Roman Curia rather than as a descriptive travel account. Written in the aftermath of Possevino’s 1583 mission to Transylvania, the Commentario was designed to evaluate the political, confessional, and institutional conditions under which a Catholic restoration might become feasible in a fragmented early modern principality. The analysis shows that Possevino conceptualized Transylvania as a space of confessional fluidity rather than fixed religious alignment. In his assessment, religious pluralism, estate-based political structures, and the limited authority of the prince did not merely constrain Catholic renewal but also created specific openings for long-term intervention. Accordingly, the Commentario does not promote coercive conversion. Instead, it outlines a gradual strategy centred on education, elite formation, and the reconstruction of ecclesiastical institutions while repeatedly emphasizing the weakened organizational state of the local Catholic Church as the principal obstacle to reform. A separate section examines Possevino’s reflections on the Orthodox Romanian population, whom he regarded as both socially marginalized and numerically significant. By analysing his arguments concerning origin, language, and ecclesiastical organization, the article demonstrates how historical and linguistic reasoning was mobilized to legitimize a pragmatic missionary approach that sought union with Rome without abandoning the Eastern rite. Methodologically, the study situates the Commentario within the broader context of Jesuit information practices and Roman decision-making processes. Engaging critically with both Hungarian and Romanian historiography, it interprets Possevino’s text as a purpose-driven intervention shaped by institutional priorities and reads early modern Transylvania as a terrain of ongoing confessional negotiation rather than confessional settlement.